Intra-party democracy from members’ viewpoint: the case of left-wing parties in Portugal - Sanches, Edalina (2017)
Focusing on the Portuguese case, this article aims to examine how members evaluate items of intra-party democracy and the ways in which their evaluations vary significantly across parties and key individual-level factors. It uses data from online surveys conducted in 2014 to grassroots members of three left-wing parties that differ in their organisational and participative profiles: the centre-left Socialist Party and the radical left Left Bloc and Livre. The results reveal more positive evaluations among members of radical left parties and for those featuring higher levels of activism and ideological congruence with the party. However, appraisals tend to be more negative when there are higher expectations of influencing the candidate selection process and of gaining professional benefits through membership. The findings suggest that democratising reforms may be a double-edged sword by attracting members who value this kind of change but at the same time fostering critical appraisals.